Pengaruh Product Placement Dalam Drama Korea Terhadap Brand Awareness Produk Kopiko - Shabirah, Nuha Inas; Jannah, Miftahul (Management Department of Economics and Business Of Trunojoyo Madura University, 2025)
This research aims to determine the influence of product placement in Korean drama on brand awareness of Kopiko products. Purposive sampling technique was used to take sample from fans of Korean dramas on @kdrama_menfess account in social media X. Data collection was carried out by distributing questionnaires and measuring using a Likert scale. This research uses multiple linear regression analysis with the statistical package for social sciences (SPSS) to determine the influence of product placement in Korean dramas on brand awareness of Kopiko products. In this research, the results showed that placement prominence in Korean drama does not have significant effect on brand awareness of Kopiko products with a significance value of 0.444 0.05. Plot connection in Korean drama had a significant effect on brand awareness of Kopiko products with a significance value of 0.000 0.05. Auditory placement in Korean drama does not have significant effect on brand awareness of Kopiko products with a significance value of 0.924 0.05. product placement Kopiko in Korean drama simultaneously have a significance influence on brand awareness with a significance value of 0.000 0.05.